Mineral Composition of Seed, Seed Hull, and Pod of African Locust Bean “Parkia Biglobosa” - Jacob, Mathew; Amuda, A. J.; Umaru, Isaac John (Darul Yasin Al Sys, 2024)
The study was conducted to determine the mineral composition of different part of African locust bean (Parkia biglobosa) tree utilized by man and animal. The experiment was carried out at Federal University Wukari Teaching and Research Farm. The samples of different part of African locust bean (Parkia biglobosa) tree were collected within the Federal University environment. The different part collected were as follows: Seed, Pod, Seed hull, and each one serves as a treatment (T1...T3). Samples collected were oven dried and milled for laboratory analysis to determine the mineral composition using standard techniques. The following minerals were (Calcium (Ca), Phosphorus (P), Magnesium (Mg), Sodium (Na), Potassium (K), Zinc (Zn), Iron (Fe), Manganese (Mn), Selenium (Se), Sulphur (S) and Copper (Cu)). Data obtained were subjected to analysis of variance (ANOVA) using SPSS version 23.0.2018. The results of analysis showed that the mineral composition are; (P (0.28-0.36%), Ca (0.19-0.23%), K (0.35-0.72%), Na (0.19-0.22%), S (0.37-0.48%), Cu (13.57-21.47 mg/kg), Fe (118.80-138.07 mg/kg), Se (0.04-0.07 mg/kg), Mn (37.30-52.57 mg/kg), Zn (58.50-81.57 mg/kg)) showed that T1 (seed) had the highest values of all the mineral analysed except Mg (0.22-0.27%) followed by T3, Seed hull. The mineral composition was observed to have varied significantly (P<0.05) across the treatments which could be attributed to different parts of Parkia biglobosa examined. In conclusion, mineral composition of the African locust bean (Parkia biglobosa) tree parts, were lower than the tolerance level. Consequently, ruminant farmers can include seed hull, and pod in formulating ration for their livestock.